Temporal trends in online searches related to COVID-19 vaccine safety: A digital infodemiology study - Akshaya Srikanth Bhagavathula; Theodoros Daglis; Vijay Kumar Chattu (Tabriz University of Medical Sciences, 2024)
Background: The rapid development of COVID-19 vaccines may have raised public concerns about their safety and side effects in the United States (US). This study aimed to assess trends in online searches related to the safety and side effects of COVID-19 vaccines in the US from 2021-2022. Methods: Google COVID-19 Vaccination Search Insights was used to analyze searches about COVID-19 vaccine safety and side effects in the US from January 4, 2021, to November 21, 2022 (98 weeks). Data were scaled from 0 (low interest) to 100 (high interest) as a fixed scaling factor called scaled normalized interest (SNI) to indicate relative search interest over time and by location. A joinpoint regression analysis was used to determine the search trends during the study period. Results: Analysis included 709 counties across 38 US states. Searches of COVID-19 vaccine safety and side effects peaked in April 2021 in the District of Columbia (SNI: 35.8), Massachusetts (29.7), New Hampshire (27.4), Connecticut (27.3), and Maine (26.7), then decreased significantly by an average monthly percentage change (AMPC) of -16.6% (95% CI -19.9 to -13.3) until July 2022. Overall AMPC from January 2021 to November 2022 was -8.9% (95% CI -16.2 to -0.9; P<0.001). Conclusion: Online searches related to COVID-19 vaccine safety and side effects decreased dramatically over time, supporting the utility of digital surveillance to track real-time vaccine safety concerns. This study provides insights into public interest in COVID-19 vaccine risks and can help monitor potential safety issues.